Latin American Health Regimes in the Face of the Pandemic - Ilán Bizberg (Revue Interventions Économiques)
None of the Latin American countries has achieved fully universal, egalitarian, and efficient health systems, although Uruguay and Costa Rica have probably come closest to this goal. The pandemic the world is currently undergoing has strained all the health organizations of the continent; an exceptional situation that allows us to compare their performance and resilience. It is clear that some countries have weathered the crisis better than others in part due to the condition of the health services themselves, but also from the approach that different governments adopted to deal with the epidemic. I will analyze three aspects: 1. The specific trajectories of the different health systems, and more particularly the changes they underwent since the beginning of the commodity boom and the arrival to power of redistributive coalitions in certain countries; 2. The specific characteristics of the different health organizations in terms of coverage, structure, investment, infrastructure, and historical performance; and 3. The performance of the various health regimes during the pandemic.